Analisis Yuridis Kontradiksi Perlindungan Konsumen dalam Konflik Kepentingan Ekonomi Aplikasi Shopee Terhadap Pertanggungjawaban Hukumnya - Otaviola, Elda; Wardhani, Sri Pramudya (Syntax Literate, 2026)
The development of digital technology has created electronic trading platforms such as Shopee, which now dominates the e-commerce market in Indonesia with 53.22% of users. However, this has also raised legal issues related to consumer protection in online transactions. This study aims to analyze Shopee's non-compliance as a platform provider with its legal obligations under the Consumer Protection Law (UUPK) No. 8 of 1999 in guaranteeing consumer rights. In addition, this study also seeks to formulate Shopee's legal responsibility to ensure that consumers' rights to compensation and damages are fulfilled. The method used is normative juridical with a case study approach. The analysis is conducted on laws and regulations, particularly UUPK No. 8 of 1999 and Article 1367 of the Civil Code, as well as literature related to consumer protection and the theory of vicarious liability from Philipus M. Hadjon. The data was obtained through a literature study covering primary, secondary, and tertiary legal materials, as well as analysis of real cases from Media Konsumen Indonesia (Indonesian Consumer Media) that show a systematic pattern of responsibility avoidance by the platform. The research findings reveal that Shopee is not in compliance with the UUPK. This is evident from the lack of supervision of sellers, complicated and opaque refund procedures, and an internal dispute resolution system that tends to be unfair. These conditions violate Article 4 paragraph 8, Article 7, Article 8, and Article 19 of the UUPK. The contradiction between economic interests based on transaction commissions and consumer protection responsibilities causes platforms to tend to evade responsibility, even though they have full control over their operational systems. This study recommends the application of the principle of vicarious liability, based on Article 1367 of the Civil Code, with tiered sanctions. In addition, it is recommended to strengthen seller verification, establish a guarantee fund system, an independent dispute resolution mechanism, and proactive supervision. These steps are expected to balance digital economic innovation with effective consumer protection.